Personalized Medicine in Epidemics - Middelburg, Rutger A. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This reprint contains 11 chapters on a wide range of subjects related to the impacts of different types of epidemics on our ability to practice personalized medicine. Together, these chapters provide a broad overview with many different examples of epidemics. The personalization of medicine is present both despite and because of epidemics. Many more examples are possible, but this reprint offers a primary overview emphasizing the widely spread relevance of the topic.